2013
DOI: 10.1002/cne.23215
|View full text |Cite
|
Sign up to set email alerts
|

Representation of the visual field in the primary visual area of the marmoset monkey: Magnification factors, point‐image size, and proportionality to retinal ganglion cell density

Abstract: The primary visual area (V1) forms a systematic map of the visual field, in which adjacent cell clusters represent adjacent points of visual space. A precise quantification of this map is key to understanding the anatomical relationships between neurons located in different stations of the visual pathway, as well as the neural bases of visual performance in different regions of the visual field. We used computational methods to quantify the visual topography of V1 in the marmoset (Callithrix jacchus), a small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
59
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 99 publications
11
59
1
Order By: Relevance
“…We also confirmed that, as in other primates (e.g. Silveira et al, 1989;Azzopardi and Cowey, 1993) the representation of the visual field in V1 deviates significantly from that expected solely on the basis of the retinal ganglion cell density, with relatively more V1 neurons dedicated to the representation of the foveal space (Chaplin et al, 2013a).…”
Section: The Representation Of the Visual Field In V1supporting
confidence: 78%
See 3 more Smart Citations
“…We also confirmed that, as in other primates (e.g. Silveira et al, 1989;Azzopardi and Cowey, 1993) the representation of the visual field in V1 deviates significantly from that expected solely on the basis of the retinal ganglion cell density, with relatively more V1 neurons dedicated to the representation of the foveal space (Chaplin et al, 2013a).…”
Section: The Representation Of the Visual Field In V1supporting
confidence: 78%
“…If this is the case, the map is anisotropic (Van Essen et al, 1984;Gattass et al, 1987). Although we did observe anisotropy in marmoset V1 (Chaplin et al, 2013a), it was small in magnitude and appeared to vary slightly from case to case. For simplicity, an estimate of M, assuming no anisotropy, can be expressed as…”
Section: The Representation Of the Visual Field In V1contrasting
confidence: 60%
See 2 more Smart Citations
“…[34] This overrepresentation of the central visual field is largely formed at the retinal level and preserved in the OR. [35] Assuming uniform distribution of lesions within the OR, it is likely that OR fibers sub-serving central vision are damaged more extensively, which, in turn, may cause larger damage of the central (temporal) RNFL.…”
Section: Discussionmentioning
confidence: 99%